Teori Motivasi Mcclelland dan Implikasinya dalam Pembelajaran PAI - Muhammad Ridha (PALAPA, 2020)
The issue of learning achievement for students needs to be an important discussion because it can affect the education of a nation. Among the causes of low student achievement is motivation. All parties involved in education should contribute to solving the problem. This article aims to explore McClelland's motivational theory and actualize it in Islamic education (PAI) learning. The approach used is a qualitative approach by conducting literature studies or library research in accordance with the theme of the main topic. The analysis used is discourse analysis to examine the value or message contained in a text, especially about McClelland's achievement motivation theory and PAI learning. The results of this study indicate that PAI learning should contain McClelland's motivation regarding achievement motivation, power motivation, and affiliation motivation to support the interests of students. This is also supported by the argument from the Qur'an and the Hadith.